Strategi manajemen perubahan yang efektif dalam menghadapi tantangan di era digital - Arridlo, Muhammad (Maliki Interdisciplinary Journal, 2025)
The concept of change management has become crucial for organizations aiming to thrive in dynamic and competitive environments. Effective change management strategies help organizations to adapt and implement necessary transformations successfully while minimizing resistance. This paper explores the strategies for managing change effectively, focusing on key approaches such as communication, leadership involvement, employee engagement, and the role of organizational culture. By examining various models and case studies, the paper highlights best practices and challenges faced by organizations in the change process. The findings suggest that a comprehensive and tailored approach, with clear communication and strong leadership, is essential for overcoming resistance and achieving sustainable success. The study contributes to the understanding of how strategic management of change can enhance organizational resilience and performance.